Issue of Halalan Toyyiba in food supply chain among food handlers / Nurul Asmida Saad and Mohd Anuar Ramli - Saad, Nurul Asmida; Ramli, Mohd Anuar (Academy of Contemporary Islamic Studies (ACIS), Universiti Teknologi MARA (UiTM), 2019)
In the Halalan Toyyiba food supply chain, the polls regarding contamination often occur involving prohibited elements or elements that endanger human health and safety. According to the World Health Organization (WHO), various cases of contamination and food poisoning have been reported worldwide which have resulted in poor health conditions and endangering human lives. Typically, diarrhoea is the most widely reported illness. It causes 550 million people to fall ill and 230,000 deaths annually. In Malaysia, there are also reported cases of contamination and food poisoning. It involves food contamination in school canteens, wedding caterings, and dining outlets. The cases have shown that there was a neglect on the aspects of halalan toyyiba in the food supply chain among food handlers. In Islam, the negligence of taking halalan toyyiba food affect both physical and spiritual aspects of individual. Hence, this study adopted qualitative method by using library research where literature and cases related to food contamination in Malaysia from press reports and the Ministry of Health data has been refered to. Researchers also interviewed 11 informants involved in food handling around the Klang Valley. The study showed that neglecting halalan toyyiba food handling practices (HTFHP) in the food supply chain lead to halal and toyyib-aspect contamination from the farm to the table such as external raw food contamination, contamination caused by cleaning processes, food packaging contamination, food storage contamination, contamination during food transport, and contamination during food storage. Therefore, there is a need for an awareness on food handling among food operators to ensure that food handling is practiced in accordance with HTFHP, and it protects consumer from eating foods containing prohibited and harmful substances.